Physical Literacy Assessment of Elementary School Children in Indonesian Urban Areas - Suntoda, Andi; Anira, A; Nugroho, Wildan Alfian; Wibowo, Ricky (Universitas Pendidikan Indonesia, 2021)
Currently, physical literacy recognizes as a critical part of physical education. The purpose of this study was to measure Physical Literacy Elementary School Children in Indonesian Urban Areas, a total of 60 students (23 girls, 38.3%; 37 boys, 61.7%) grade 5 (aged 11-12 years) as a participant for survey studies. The instrument used to measure PL is the Canadian Assessment of Physical Literacy (CAPL). It's used survey research methods. The analysis technique in this study uses descriptive statistical analysis to investigate the results of students' physical literacy based on the data that has been collected—technical data analysis using SPSS software. The result showed that students have good motivation and confidence. However, the level of knowledge and understanding of data is still relatively low, as well as the physical competence.